IN VITRO INVESTIGATION OF THE TRANSPLANTATION PROSPECTS OF MULTICELLULAR SPHEROID MICROAGGREGATES OF DONOR RETINAL PIGMENT EPITHELIUM - S. A. Borzenok; I. A. Popov; I. N. Saburina; P. M. Arbukhanova (Вестник трансплантологии и искусственных органов)
Aim. To study in experiment the criteria for transplantability of multicellular spheroid microaggregates of retinal pigment epithelium (RPE), prepared by the method of 3D cell culture. Materials and Methods. 11 donor eyes (6 of adrenaline index «A», 5 of index «B») were used as a source of RPE cell cultures (group «A» – 6 cultures, group «B» – 5 cultures), of which over 2000 RPE spheroids were obtained by the method of three-dimensional cell culture. 1760 spheroids of them were selected for transplantability investigation (960 – group «A», 800 – group «B»). Among the selected spheroids were equal numbers of spheroids of different morphology («smooth» and «rough») and of the initial cell seeding number (500, 1000, 5000, 25 000, 125 000 cells per hanging drop). We were taking out 12 spheroids of group «A» and 10 spheroids of group «B» of the 3D culture in terms of 7, 14, 21, 28 days of 3D culture to assess their viability. We were transferring the same number of spheroids in the same terms from 3D to 2D culture conditions to assess their adhesive properties. Viability of cells within spheroids was determined using the Trypan blue exclusion. The presence or absence of adhesion was determined by microscopic observation.Results. «Smooth» spheroids of 7 and 14 days of pretransplantation cultivation and derived from hanging drops containing 500 and 1000 cells showed the highest transplantability (cell viability varied from 0.83 ± 0.38 to 0.94 ± 0.24, a 100% adhesion). «Rough» spheroids were untransplantable in all variants, despite their partial preservation of viability (in comparison to “smooth” ones p < 0.05). 21 and 28 days of pretransplantation culturing and high cell seeding numbers signifi cantly lowered transplantability of obtained spheroids (p > 0.05 for low cell numbers, p < 0.05 for the high ones). Differences in adrenaline indexes A and B of donor eyes which were the primary sources of cellular material had no effect (p > 0.05) on resulting spheroids transplantability.Conclusion. Among RPE spheroids obtained by our method the spheroids cultivated in a 3D environment for 7 to 14 days prior to transplantation and derived from hanging drops containing 500 and 1000 RPE cells showed the highest transplantability.